Long-distance movements of an unprotected population on the Laikipia Plateau, Kenya - Chris Thouless (Pachyderm)
Results from radio tracking 20 elephants over a two year period suggest the approximately 3000 animals presently in the area are comprised of 4 main subpopulations: the Laikipia residents, the itinerant Laikipia elephants which are the main crop raiders, the forest dwellers which move onto the plains after the rain and the long distance migrants which move between Samburu and Laikipia two times a year. The apparent migration, which is probably no more than 20 years old, may have initially been a response to poaching. Now its occurence is associated with land use conflict and water accessibility.